High-Performance Finned Tubes for Production Facility Heating Systems - A. Usenkov, Roman; ., . (International Journal of Engineering and Technology, 2018)
The values of the optimal height of the ribs and their optimal placement step on the surface of the heating device are determined. It was possible to determine that the installation of rectangular rods with a step of 8.2 mm on the surface at an angle of 90 degrees to the horizon, leads to an increase in the local coefficient of convective heat transfer to 200% compared to the surface on which there are no rods. It was found that the simplexÂ Â  acts as a separate parameter that affects the local coefficient of convective heat transfer on a surface with rectangular bars.Â